Increased Lipid Synthesis and Decreased β‐Oxidation in the Liver of SHR/NDmcr‐cp (cp/cp) Rats, an Animal Model of Metabolic Syndrome. Issue 11 (18th September 2013) - Tanaka, Shizuyo; Yamazaki, Tohru; Asano, Satoshi; Mitsumoto, Atsushi; Kobayashi, Daisuke; Kudo, Naomi; Kawashima, Yoichi
Abstract: SHR/NDmcr‐cp ( cp / cp ) rats (SHR/NDcp) are an animal model of metabolic syndrome. A previous study of ours revealed drastic increases in the mass of palmitic (16:0), oleic (18:1n‐9), palmitoleic (16:1n‐7), cis ‐vaccenic (18:1n‐7) and 5, 8, 11‐eicosatrienoic acids in the liver of SHR/NDcp. However, detailed information on the class of lipid accumulated and the mechanism responsible for the overproduction of the accumulated lipid in the liver was not obtained. This study aimed to characterize the class of lipid accumulated and to explore the mechanism underlying the lipid accumulation in the liver of SHR/NDcp, in comparison with SHR/NDmcr‐cp (+/+) (lean hypertensive littermates of SHR/NDcp) and Wistar Kyoto rats. In the liver of SHR/NDcp, de novo synthesis of fatty acids (16:0, 18:1n‐9 and 16:1n‐7) and triacylglycerol (TAG) synthesis were up‐regulated and fatty acid β‐oxidation was down‐regulated. These perturbations of lipid metabolism caused fat accumulation in hepatocytes and accumulation of TAG, which were enriched with 16:0, 18:1n‐9 and 16:1n‐7, in the liver of SHR/NDcp. On the other hand, no changes were found in hepatic contents of diacylglycerol and unesterified fatty acid (FFA); among FFA, there were no differences in the hepatic concentrations of unesterified 16:0 and stearic acid between SHR/NDcp and two other groups of rats. Moreover, little change was brought about in the expression of genes responsive to endoplasmic reticulum stress in the liver of SHR/NDcp. These results may reinforce the pathophysiological role of stearoyl‐CoA desaturase 1 and fatty acid elongase 6 in the liver of SHR/NDcp.